1989
DOI: 10.1017/s0265051700007002
|View full text |Cite
|
Sign up to set email alerts
|

The Generalist Primary Teacher of Music: a Problem of Confidence

Abstract: Why don't more primary teachers teach music? This article describes a study of forty non-specialist primary B.Ed, students over their year-long professional music course. Initially, most students have little confidence in their ability to teach music. As the course progresses, a smaller proportion of students who lack confidence teach music during school experience. A cycle has developed in which student teachers worried about music do not learn to teach it because teachers with similar worries often do not te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
5

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 0 publications
1
78
0
5
Order By: Relevance
“…There has been a long-standing debate as to whether primary school music is best taught by music specialists or nonspecialist class teachers (Wheway, 2006;Hennessy, 2006). Mills (1989) warned against the overuse of specialists suggesting that 'having a special teacher for music does not necessarily improve its image'. She suggested that children valued the subject less if it was not taught by their own class teacher as part of their whole curriculum and suggested that 'generalist teaching allows greater opportunity for music to take place as the need arises… because a class teacher has knowledge of individual children which a visiting specialist teacher cannot hope to match.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a long-standing debate as to whether primary school music is best taught by music specialists or nonspecialist class teachers (Wheway, 2006;Hennessy, 2006). Mills (1989) warned against the overuse of specialists suggesting that 'having a special teacher for music does not necessarily improve its image'. She suggested that children valued the subject less if it was not taught by their own class teacher as part of their whole curriculum and suggested that 'generalist teaching allows greater opportunity for music to take place as the need arises… because a class teacher has knowledge of individual children which a visiting specialist teacher cannot hope to match.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research into music education (Fromyhr, 1995;Mills, 1989;Russell-Bowie, 1993;Ryan, 1991) indicates that the majority of pre-service primary teachers enter their teacher education courses having minimal, if any, formal music education experience, either from school or from outof-school activities. Lephard (1995) adds to these observations, indicating that many pre-service primary teachers have little musical literacy and the university time allocated for music education is inadequate to sufficiently prepare confident and competent teachers in music education.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore vital to have a qualified teacher overseeing music lessons. Generalist teachers, or teachers with limited musical experience, have shown a greater capability to deliver a quality music education than, say, music specialists with limited teaching experience (Ofsted, 2012: 18-19), although studies continually address issues about confidence in teaching the subject (Mills, 1989;Hennessy, 2000;Seddon and Biasutti, 2008;Hallam et al, 2009;RussellBowie, 2009;Biasutti, 2010;Garvis, 2013;de Vries, 2013;Biasutti et al, 2015). Furthermore, the teaching of composition is a reported source of uncertainty for specialist as well as generalist teachers (Winters, 2012).…”
Section: Creativity and Curriculummentioning
confidence: 99%